PENINGKATAN KESADARAN HUKUM PEREMPUAN TERHADAP KEKERASAN DALAM RUMAH TANGGA DAN MASALAH SOSIAL MODERN MELALUI SOSIALISASI DI KELURAHAN NGRINGO, KABUPATEN KARANGANYAR - Kurnia Pradana, Aditya Fajri; Susetyo, Danny Trisno; Purwanti, Asri (Jurnal Indonesia Mengabdi, 2025)
This community service activity aims to increase women's legal understanding and social awareness of domestic violence (KDRT) and modern social challenges such as online loans and drug abuse. The targets of the activity were PKK mothers in Ngringo Village, Jaten District, Karanganyar Regency, who play an important role in maintaining family resilience and being the first protector for children. The implementation method used a participatory approach through legal socialisation, interactive discussions, and questions and answers with academic speakers and legal practitioners. Data was collected descriptively qualitatively through observation, documentation, and participants' responses during the activity. Results showed a significant increase in participants' understanding of the types of domestic violence (physical, psychological, economic), reporting procedures and legal protection, as well as awareness of the dangers of illegal online loans. The discussion also revealed various real-life cases relevant to people's lives, such as economic neglect, spousal drug abuse, and marital property conflicts. Participants showed great enthusiasm and began to understand the role of the law in protecting family rights. This activity contributed to the strengthening of legal literacy, the courage to report, and the development of a more just and law-aware society. In conclusion, community-based legal socialisation is effective in encouraging social transformation towards families that are harmonious, safe, and protected from violence.